Endovascular treatment to boost AV fistula maturation. Issue 1 (March 2017) - Kamper, Lars; Haage, Patrick
Impaired fistula maturation is associated with puncture-related complications, insufficient dialysis and potential permanent access failure. Non-maturation is frequently initiated by stenotic vascular access vessels comprising the outflow veins, the arteriovenous anastomosis and infrequently the inflow artery. Further findings in maturation protraction are central venous stenoses or accessory outflow veins. Depending on the underlying pathology, several endovascular approaches to boost fistula maturation are possible. To date standard balloon angioplasty remains the primary proven treatment option.